Pathophysiological association of catecholamine stress in a patient with Takotsubo cardiomyopathy and chronic kidney disease : a case report = Patofiziološka povezanost katekolaminskog stresa kod pacijentice s Takotsubo kardiomiopatijom i kroničnim zatajenjem bubrega : prikaz slučaja - Vučić, Domagoj, liječnik (Array, 2021)
Aim: Takotsubo cardiomyopathy is a transient dysfunction of the heart muscle that occurs in response to a stressful event. A working diagnosis is mostly made for acute ischemic heart disease due to similar clinical presentation and differential diagnostic doubts. Although it is a reversible disorder of cardiac contractility, mortality rate is similar to that of an acute coronary syndrome due to the development of complications. We report the case of a patient with chronic kidney disease and the consequent development of Takotsubo cardiomyopathy, a possible pathophysiological link that has not been reported in the significant number in literature so far. Case report: An 83-year-old patient on a chronic hemodialysis program, due to the development of anginal symptoms specific for the acute coronary syndrome and with a significant increase in cardiospecific enzymes, was transferred to the Coronary care unit for the necessary invasive cardiac treatment. Echocardiographic and coronarographic findings confirmed the diagnosis of Takotsubo cardiomyopathy, which was the first case in a patient on chronic hemodialysis program in our institution. Conslusions: According to available data, about 30 cases of Takotsubo cardiomyopathy have been reported so far, indicating that transient myocardial dysfunction is a rare cardiomyopathy in patients with chronic kidney disease. A small number of literature-recorded cases do not support the similar pathophysiological basis of increased sympathetic activity present in Takotsubo cardiomyopathy and chronic kidney disease.